Back to Me: Conversational narcissism and its amelioration in couples therapy (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
Conversational narcissism, or self-oriented and other-neglecting habits of speaking and listening are common in intimate relationships, with deleterious effects. The same can be said about communication style mismatches, where partners normalize their own expressive habits and abnormalise those of their mate. The task in couples therapy is to help partners fine tune speaking with a listener in mind, and listening with a speaker in mind.
Keywords: Conversational narcissism; responsible responding; communication style mismatches; couples therapy